Tough customer (Thorndike Press large print basic, ,, 2010)
Entreated by his former lover, Caroline, to help protect her daughter from a depraved man who has been stalking her, staff investigator Dodge Hanley teams up with a small-town sheriff and enlists methods from his own shady past to find answers.

Blind tiger ([Hachette Audio], Grand Central Publishing Large Print, Grand Central Publishing, 2021)
"Thatcher Hutton, a war-weary soldier on the way back to his cowboy life, jumps from a moving freight train to avoid trouble . . . and lands in more than he bargained for"--

Smash cut (Thorndike Press large print basic, ,, 2009)
Hired by a woman who believes that the accidental shooting of a friend was actually orchestrated by the victim's depraved nephew, defense lawyer Derek Mitchell comes to realize that the nephew is a psychotic movie buff who enjoys acting out violent film plots.

Thick as thieves (Grand Central Publishing Large Print, Grand Central Publishing, 2020)
"Twenty years ago in the dead of night, four seemingly random individuals pulled the ultimate heist and almost walked away with half a million dollars. But by daybreak, their plan had been shot to hell. One of them was in the hospital. One was in jail. One was dead. And one got away with it. Arden Maxwell, the daughter of the man who disappeared all those years ago, presumably with the money, after murdering his accomplice, has never reconciled with her father's abandonment of her and her sister. After countless personal setbacks she decides to return to her family home near mysterious Caddo Lake, and finally get answers to the many questions that torment her. Little does she know, two of her father's co-conspirators, a war hero and a corrupt district attorney, are watching her every move."--

Overkill (Grand Central Pub, Grand Central Publishing, 2022)
"Former Super Bowl MVP quarterback Zach Bridger hasn't seen his ex-wife, Rebecca Pratt, for years--not since their volatile marriage imploded--so he's shocked to receive a life-altering call about her. Rebecca has been placed on life support after a violent assault, and he--despite their divorce--has medical power-of-attorney. Zach is asked to make an impossible choice: keep her on life support or take her off of it. Buckling under the weight of the responsibility and the glare of public scrutiny, Zach ultimately walks away, letting Rebecca's parents have the final say. Four years later, Rebecca's attacker, Eban--the scion of a wealthy North Carolina family--gets an early release from prison. The ludicrous miscarriage of justice reeks of favoritism, and Kate Lennon, a brilliant state prosecutor, is determined to bring him to justice. Rebecca's parents have kept her alive all these years, but if her condition were to change--if she were to die--Eban could be retried on a new charge: murder. Kate's mission to send Eban back to prison for good depends wholly on Zach. It isn't lost on him that in order for Eban to be charged with Rebecca's murder, Zach must actually be the one to kill her. He rejects Kate's legal standpoint, but can't resist their ill-timed attraction to each other. Eban, having realized the jeopardy he's in, plots to make certain that neither Zach nor Kate lives to see the death of Rebecca--and the end of his freedom." --